Peranan Pengelolaan Keuangan sebagai Pertanggungjawaban dalam Pembelanjaan Dana Desa Sesuai Standar Akuntansi Pemerintah di Desa Bah Jambi III Kecamatan Tanah Jawa Kabupaten Simalungun - Khoirunisa, Afifah Aulia; Arif, Muhammad; Nasution, Juliana (ManBiz: Journal of Management and Business, 2024)
This study aims to identify and describe the Role of Financial Management as Accountability in Spending Village Funds According to Government Accounting Standards in Bah Jambi III Village, Tanah Jawa District, Simalungun Regency. Method The approach in this research is a qualitative approach with a descriptive research type. The data sources used are primary data obtained by interviews and direct observation and secondary data obtained from related documents. The research location is located in Bah Jambi III Village, Tanah Jawa District, Simalungun Regency. The results of this study indicate that: (1) The village financial management mechanism is regulated in Law Number 6 of 2014 concerning Villages which explains that there are 5 cycles of financial management mechanisms, namely. planning, implementation, administration, reporting, accountability. (2) While the obstacles faced by the village government are low human resource capacity, disbursement of village funds, government. (3) In Application of Government Accounting Standards No. 01 in village financial accountability. Reporting and financial accountability have not implemented Government Accounting Standards No. 01, because the Financial Report for accountability made by Bah Jambi III Village